The Effect of Financial Knowledge and Financial Attitudes on Financial Behavior through Financial Literacy - Qordhowi, Yusuf; Ratnawati, Kusuma (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The rapid development of digital technology in the era of Industrial Revolution 4.0 has transformed lifestyles, particularly among Generation Z, who tend to exhibit more consumptive behavior and face challenges in managing personal finances. This condition highlights the importance of understanding the factors that influence students’ financial behavior as part of the productive-age population. This study aims to examine the effects of financial knowledge and financial attitudes on financial behavior, with financial literacy serving as a mediating variable among Generation Z students at Universitas Brawijaya. This study adopts a quantitative approach using a survey method involving 375 undergraduate and postgraduate students. Data were collected through a Likert-scale questionnaire and analyzed using SEM-PLS. The results indicate that financial knowledge and financial literacy have a significant effect on financial behavior, whereas financial attitudes do not have a significant direct effect. However, financial literacy is found to play a significant mediating role, indicating that financial knowledge and financial attitudes indirectly influence financial behavior through financial literacy. The study concludes that enhancing financial literacy is a key factor in shaping healthy financial behavior among Generation Z students and should be prioritized within higher education to support students’ long-term financial well-being.